Dexmedetomidine Inhibits Gasdermin D-Induced Pyroptosis via the PI3K/AKT/GSK3β Pathway to Attenuate Neuroinflammation in Early Brain Injury After Subarachnoid Hemorrhage in Rats - Wei, Boyang; Liu, Wenchao; Jin, Lei; Guo, Shenquan; Fan, Haiyan; Jin, Fa; Wei, Chengcong; Fang, Dazhao; Zhang, Xin; Su, Shixing; Duan, Chuanzhi; Li, Xifeng (Frontiers in Cellular Neuroscience, 2022)
Subarachnoid hemorrhage (SAH) is one kind of life-threatening stroke, which leads to severe brain damage. Pyroptosis plays a critical role in early brain injury (EBI) after SAH. Previous reports suggest that SAH-induced brain edema, cell apoptosis, and neuronal injury could be suppressed by Dexmedetomidine (Dex). In the present study, we used a rat model of SAH to investigate the effect of Dex on pyroptosis in EBI after SAH and to determine the mechanisms involved. Pyroptosis was found in microglia in EBI after SAH. Dex significantly alleviated microglia pyroptosis via reducing pyroptosis executioner GSDMD and inhibited the release of pro-inflammatory cytokines induced by SAH. Furthermore, the reduction of GSDMD by Dex was abolished by the PI3K inhibitor LY294002. In conclusion, our data demonstrated that Dex reduces microglia pyroptosis in EBI after SAH via activation of the PI3K/AKT/GSK3β pathway.